Fascist visions : art and ideology in France and Italy - Affron, Matthew, 1963-; Antliff, Mark, 1957- (Princeton University Press, 1997)
Bringing together studies by art historians, historians, and political scientists, Fascist Visions explores the themes and paradigms that pervaded protofascist and fascist aesthetic discourse, cultural policy, and artistic production in France and Italy. Whether traditionalist or innovative in idiom, art expressed fascism's ideological polarities: nihilism and idealism, modernism and antimodernism, revolution and reaction. This volume charts the unfolding of fascist aesthetics from its genesis in nationalist and antimaterialist ideologies before World War I to its full development during the interwar period and World War II. It also highlights the shared motivations of advocates of fascist aesthetics, including artists, art critics, political activists, and government officials, outside of Germany.
Keywords: Le Corbusier -- 1887-1965; Saint-Point, Valentine de -- 1875-1953; Sironi, Mario -- 1885-1961; Soffici, Ardengo -- 1879-1964; Valois, Georges -- 1878-1945; Soffici, Ardengo.; Saint-Point, Valentine de.; Sironi, Mario.; Valois, Georges.; Le Corbusier.; Fascism and art -- France.; Art and state -- France.; Fascism and art -- Italy.; Art and state -- Italy.; Fascisme et art -- France.; Art -- Politique gouvernementale -- France.; Fascisme et art -- Italie.; Art -- Politique gouvernementale -- Italie.; 20.10 art and society: general.; ART -- Individual Artists -- General.; Art and state; Fascism and art; France; Italy; Faschismus; Kunst; Kunstpolitik; Frankreich; Italien; Vichy-Regime; Aufsatzsammlung; Kunst.; Fascisme.; Art and state -- France -- History -- 20th century.; Art and state -- Italy -- History -- 20th century.; France.; Italy.; Fascism.; Cultural property.; Cultural heritage.; Art et État -- Italie.; Aufsatzsammlung.